디지털 기술과 웹툰의 재매개 - 고민정(Ko, Min Jung) (문화콘텐츠연구, 2016)
현대의 미디어들은 모두 다른 미디어들과 상호작용하며 서로의 특성을 차용하고 변형함으로써 새로운 미디어적 특성을 획득하는 과정을 거듭하고 있다. 웹툰 역시 새로운 플랫폼에 적응하며 끊임없이 다른 매체의 특성들을 받아들이며 변화함으로써, 고유의 특성들을 재정의하고 새로운 형식의 웹툰을 탄생시켰다. 디지털 기술을 활용한 웹툰의 표현 양식의 변화는 독자/사용자의 미적 경험에도 영향을 미치는데, 웹툰에 적용된 멀티미디어 효과는 시각 뿐 아니라 청각, 촉각을 자극함으로써 독자/사용자의 몰입도를 높이는 한편, 매체 자체에 대한 각성을 통해 새로운 미적 경험을 제공한다. 본 논문은 볼터와 그루신의 ‘재매개’ 개념을 통해 웹툰이 어떤 방식으로 다른 매체의 특성들을 차용하고 변형하여 자신의 것으로 만드는지, 이를 통해 독자/사용자에게 어떤 영향을 미치는지 살펴보고자 한다. Current entertainment media forms interact with one another through remediation, and take a “property” from one medium and reuse it in another to establish their own. By adapting to the new platform, webtoons remediate other media, such as print comics, animation, web fiction. The changes in style/format of webtoons influence reader/user experience. Webtoons stimulate the senses of sight, smell, hearing, touch with multimedia effects such as flash, gif animations, background music, and vibration of phone to increase immersion. Meanwhile, those effects make reader/user recognize that medium(webtoon) itself. This essay will explore how webtoons remediate, redefine and revitalise their own forms by drawing upon other media in Bolter and Grusin's concept of remediation, and how the remediation of webtoons provides to reader/user aesthetic experiences. KCI Citation Count: 9